Cross-cultural adaptation and validation of the malocclusion impact questionnaire for patients seeking orthodontic treatment - Shoroog Agou; Ghadir Al-Sakkaf; Lujain Barboud; Mustafa Elhussein (Wolters Kluwer Medknow Publications, 2022)
OBJECTIVES: To assess the adaptability and validity of the Arabic version of the Malocclusion Impact Questionnaire (MIQ-AR) in patients seeking orthodontic treatment. MATERIALS AND METHODS: This cross-sectional survey was conducted on a convenience sample of 77 Arabic speaking, healthy, 10-16-year-old children, selected based on their personal perception of "needing braces.". The participants completed the MIQ-AR and the Child Perceptions Questionnaire for children aged 11-14 (CPQ11-14), answered two global questions, and had their Index of Orthodontic Treatment Need, Dental Health Component (IOTN.DHC) scores recorded. Construct validity was examined by measuring the correlation between the MIQ-AR score and the responses to the two global questions. Criterion validity was examined by measuring the correlation between the MIQ-AR and both the IOTN.DHC and CPQ11-14 scores. RESULTS: Moderate positive correlations were observed between the MIQ-AR scores and the first (ρ = 0.320, P < 0.001) and second global questions (ρ = 0.388, P < 0.001). A strong positive correlation was found between the total CPQ11-14 and MIQ-AR scores (ρ = 0.597, P < 0.001). A positive gradient was observed between the MIQ-AR scores and IOTN.DHC scores. CONCLUSION: Our results indicate that the MIQ-AR is a valid tool for measuring oral health-related quality of life in patients with malocclusion, with good psychometric parameters. These preliminary findings require further testing in various settings involving a larger and more diverse sample.